PALM OIL FUEL ASH (POFA) AS AGRO-WASTE TO MODERN STABILIZATION ON SUBGRADE - Toyeb, Muhammad; Hakam, Abdul; Fauzan, Fauzan; Andriani, Andriani (JURNAL TEKNIK SIPIL, 2023)
Subgrades in low bearing capacity are often improved by traditional stabilization methods using cement and lime, that have problems with environmental issues. Because processes cement production released Carbondi-oxide (CO2) to the air. Instead, a modern stabilization is known as environmentally friendly materials, such as POFA as agro-waste. The purpose of the research was to obtain the strength of soil by adding 20% POFA. Measurement the samples consist soil properties test and CBRsoaked tests and microscopic observation (SEM). The test results obtained that added 20% POFA was able to changed soil characteristics by reduce the plasticity index of 11.20% to 3.63%% or medium to low plasticity. Then occurred decrease the MDD of 1.83 to 1.68 gr/cm3 and increase the OMC of 13.60% to 17.0%. The CBR soaked test obtained was increase the strength soil stabilization until curing of 7 days to exhibited CBR value of 3.25% to 8%. It was comply to value CBR standard for subgrade, minimum of 6%. Microscopic observations showed that the surface was coarser and POFA looks like closed togeth-er that filling the pores of soil and looks more dense. Thus, the POFA is feasible for exhibition as alternative modern stabilization material.